Preparation of a Low-Cost KCO/AlO Sorbent for CO Capture at Flue-Gas Operating Conditions - Javad Esmaili; Mohammad Reza Ehsani (Adsorption Science & Technology)
In this study, the efficiency of a low-cost K 2 CO 3 /Al 2 O 3 sorbent as a CO 2 capture support was investigated. The sorbent was prepared by impregnating K 2 CO 3 on industrial-grade Al 2 O 3 . The CO 2 capture capacity of the sorbent was calculated from the breakthrough curve of the CO 2 adsorption inside a fixed-bed reactor, in the presence of H 2 O and at an adsorption temperature of 60 °C. An adsorption capacity of 75.4 mg CO 2 /g of sorbent was obtained. The stability of capture capacity of the sorbent was higher than that of the reference sorbent. The changes in the pore volume and surface area were 0.020 cm 3 /g and 5.5 m 2 /g, respectively, after five cycles of adsorption and regeneration. However, there were minor changes in the pore-size distribution and surface area of the sorbent after five cycles. This sorbent can be considered to be used in large-scale applications.